Oral versus topical carbonic anhydrase inhibitors in ocular hypertension after scleral tunnel cataract surgery - Abdulmoghni Al-Barrag (Dove Medical Press, 2009)
Abdulmoghni Al-Barrag1, Motaher Al-Shaer1, Nabil Al-Matary2, Mahfoud Bamashmous11Ophthalmic Department, Faculty of Medicine and Health Sciences, Sana’a University, Sana’a, Republic of Yemen; 2Ophthalmic Department, Military Hospital, Sana’a, Republic of YemenPurpose: To compare the effect of oral acetazolamide and topical 2% dorzolamide in prevention of ocular hypertension after scleral tunnel cataract surgery.Setting: Ophthalmic department, Sana’a University, Yemen Sana’a from March 2007 to October 2007.Methods: This prospective double-blind, randomized study included 150 eyes undergoing scleral tunnel cataract surgery with hard posterior chamber intraocular implantation. Methylcellulose was used as the viscoelastic in all surgery cases. Patients were assigned to one of three groups: group 1: topical gentamicin eye drops (control; n = 52); group 2: systemic acetazolamide 250 mg (n = 45); and group 3: topical 2% dorzolamide (n = 53). Acetazolamide patients received one 250 mg tablet, one hour before surgery, then half a tablet every eight hours. A topical dorzolamide 2% or gentamicin was applied in one drop one hour before surgery then every eight hours, for three days postoperatively. Intraocular pressures (IOP) were measured by Goldman applanation tonometry one hour preoperatively and 16, 24, and 48 hours postoperatively. Results: At 16 hours, IOP between the three groups increased significantly with a statistically significant p-value of 0.008, but the mean IOP of acetazolamide patients was less than other groups. IOP nearly returned to the normal level 24 and 48 hours postoperatively, but this was not statistically significant (p = 0.452 and 0.138, respectively).Conclusion: Acetazolamide offers better IOP control than topical dorzolamide 2% in preventing ocular hypertension after scleral tunnel cataract surgery. Keywords: cataract surgery, ocular hypertension, viscoelastic, dorzolamide, intraocular pressure